Victim identification and body completeness based on last known location at the World Trade Center. (November 2022) - Adams, Bradley; Warnke-Sommer, Julia; Odien, Jennifer; Soler, Angela
Abstract: This analysis focuses on the identification efforts conducted by the New York City Office of Chief Medical Examiner (NYC OCME) over a 20-year period from September 11, 2001 to September 11, 2021. Due to this unprecedented level of commitment to victim identification, a wealth of data has been collected over the two-decade period and is still being collected as identification efforts are ongoing. The results of this data analysis are not only informative for the World Trade Center (WTC) victims, but may also be instructional for other large-scale, protracted victim identification efforts. Based on available data, most victims are associated with the impact zones and higher in both towers. No correlation was observed in the overall identification rates based on last known location in the buildings, suggesting that location in the towers does not affect the likelihood of a successful identification. There was, however, a significant difference in the body completeness values observed for victims from the upper floors compared to those below the impact zones. The identification rates and body completeness values for victims onboard the two airplanes are significantly different from each other, possibly related to the varying aircraft speeds at the time of impact. Highlights: 20 years of victim identification data associated with the WTC disaster in NYC were analyzed. There was not a significant difference in identification rates based on last known location in the towers. There was a significant difference in identification rates between victims of the two planes. Victims located on lower floors had more complete bodies than victims on upper floors. Victims of AA Flight 11 had more complete bodies than UA Flight 175 victims.